Pembangunan Sistem Amaran Awal Kebocoran Gas LPG di Kedai Dobi Layan Diri - Muhammad Irsyad Subkilabli,; MOHAMED NOR, MOHD FAIZAL (Multidisciplinary Applied Research and Innovation, 2025)
LPG gas leaks can ignite fires, and these incidents occur frequently these days. The LPG gas in the air could have significant impacts with just one switch. The LPG Gas Leak Early Warning System is designed to provide earlier warning notifications to users once LPG gas leak is detected. A mobile application is built to monitor and provide earlier warning notifications to users. The IoT system is built based on the ESP32 microcontroller and the MQ-09 and DHT-11 sensors that measure the value of leaked LPG gas as well as the ambient temperature and humidity. When the value of the leaked LPG gas exceeds the specified range, the alarm will sound, and the exhaust fan will turn on, forcing out the leaked LPG gas. Early warning notifications are given to users through the WhatsApp app. In addition, users are able to monitor the state of the gas chambers through a real-time dashboard in the Blynk app. This system can ensure efficient monitoring of LPG gas tanks and ensure user safety is always guaranteed.